Preparation of Colon-Targeted Acetylharpagide Tablets and its Release Properties in vivo and in vitro - Liu, DeWen; Yan, Huijie; Kong, Yiming; You, Yun; Li, Yanling; Wang, Lixin; Tong, Yan; Wang, Jinyu (Frontiers in Pharmacology, 2018)
Ethno pharmacological relevance: Acetylharpagide is a monomeric compound extracted from Ajuga decumbens, widely used for remedying infectious and inflammatory diseases in Southern China Aim of the study: The present study designed and investigated the formulation of colon-targeted acetylharpagide tablets according to the dual controlled release mechanisms of time-delay and pH-sensitivity. Materials and Methods: The core tablets of acetylharpagide were coated with the material used in time-delay systems such as ethyl cellulose and suitable channeling agent, followed by pH-dependent polymers, polyacrylic resin II and III in a combination of 1:4. Furthermore, the release and absorption performance of colon-targets tables were evaluated in vitro and in vivo. In the in vitro tests, the optimized formulation was not released in simulated gastric fluid in 2h; the release was < 5% at pH 6.8 simulated intestinal fluids for 4h; the drug was completely released within 5h at pH 7.6 simulated colon fluid. In the in vivo tests, pharmacokinetic characteristics of the colon-targeted tablets were investigated in dogs. Results: The results indicated that the acetylharpagide tablets with the technology of colon-targeting caused delayed T max, prolonged absorption time, lower C max, and AUCINF_obs. Meanwhile, the apparent volume of distribution (Vz_F_bs) of the colon-target tablets was higher than the reference. Conclusions: These results suggested that colon-targeted acetylharpagide tablets deliver the drug to the colon. The in vitro performance of colon-targeted acetylharpagide tablet was appropriately correlated with its performance in vivo.